Nihil maius. La maximidad de Dios en el unum argumentum del Proslogion de Anselmo y en De docta ignorantia de Nicolás de Cusa (2021)
This article explores a relationship between the notion of maximitas dei in the unum argumentum of the Anselm's Proslogion and by Nicholas of Cusa's De docta ignorantia. Although the explicit anselmian allusions in works of the Cusano do not allow to speak a direct influence, it is tried to show how both authors come together in the speculative yield around the negativity of the maximitas dei.